The sustainability of the Youth Olympic Games: Stakeholder networks and institutional perspectives - Parent, M. M.; Kristiansen, E.; Skille, E. Å.; Hanstad, D. V. (International Review for the Sociology of Sport, 2015)
This paper explored the Youth Olympic Games` (YOG) potential sustainability (survival and success) through an analysis of how actors exert various forms of pressure on the YOG. Given the impact of the Olympic Games and of youth on society, it becomes important to study the newest member of the Olympic Family. Combining stakeholder, network and institutional literatures, a case study of the first Winter YOG in Innsbruck (Austria) was built by means of observations and interviews. The stakeholder network analysis revealed three central stakeholders for the YOG`s sustainability: the International Olympic Committee (IOC), the media (press and broadcast), and the athletes` parents. The institutional context was challenged by stakeholders` changing levels of relative saliency, and notably by the parents` emerging saliency. Practically speaking, YOG managers need to be diplomats in balancing pressures originating from the international (IOC) and local (parents) institutional contexts.